PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, UMUR PERUSAHAAN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN (Students' Journal of Accounting and Banking, 2015)
This study examined the analysis of the influence of the structure of profitability, company size, age companies and debt policy to the value of the company.The research was done in the Indonesia Stock Exchange (IDX) using manufacturing company going public. The purpose of this study was to determine the effect of capital structure, profitability,company size, age companies and debt policy to the value of the company .in companies listed on the Stock Exchange during the study period 2011-2013. The data obtained from the financial statements of publicly traded companies,Indonesian Capital MarketDirectory (ICMD) and IDX. The number of samples is 204 manufacturing company. Data analysis method used is multiple linear regression analysis was used to test the effect of two or more variables between the independent variables profitability,company size, age companies and debt policy to the value of the company of the companies listedin Indonesia Stock Exchange(IDX ) as the dependent variable. The results showed individual profitability, age companies and debt policy significant positive effect on the value of the company, while the company size is not significant of the value of the company.Keywords: Profitability, Company Size, Age Companies and Debt Policy To The Value Of The Company